Influence of Trichoderma harzianum on growth, yield and quality of lettuce (Lactuca sativa) grown under a hydroponic system - Lujain ALZYOUD; Yahia A. OTHMAN; Kholoud M. ALANANBEH; Jamal AYAD; Farah M. AL-AMIR (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Lettuce is a valuable source of iron, vitamins, fiber, and phenolic compounds with health benefits. Enhancing its yield while preserving these compounds is essential for improving its nutritional value. The objectives of this study were to: (1) determine the optimal stage for Trichoderma harzianum inoculation (germination vs. seedling) and (2) evaluate its impact on growth, yield, and quality traits of lettuce cultivars grown under a Nutrient Film Technique (NFT) hydroponic system. Two greenhouse experiments were conducted using one Romane cultivar (‘Nebrase’) and two Iceberg cultivars (‘Lolo-Rossa’ and ‘Lolo-Bionda’). The results showed that the three inoculation approaches of T. harzianum; at the seed stage, transplant stage (by adding T. harzianum solution to the root system) or directly adding T. harzianum spores to the nutrient solution produced comparable effects on shoot and root growth. In the NFT system, results from the winter cycle (16-24 oC), showed no significant differences, as the conditions were non-stressful. However, during the summer cycle (28-35°C), which imposed heat stress, all cultivars inoculated at the seed stage exhibited significantly higher chlorophyll content (192 vs. 162 µmol m-2), shoot fresh weight (134 vs. 91 g), leaf area (1170 vs. 840 cm2), root fresh weight (25 vs. 12 g), and leaf number (30 vs. 24) compared to the non-inoculated control. These findings suggest that Trichoderma enhances lettuce resilience under heat stress conditions.  In terms of cultivars, the Iceberg type ‘Lolo-Rossa’ consistently showed higher or comparable concentrations of total phenols (112-208 mg 100 g-1), flavonoids (251-505 mg 100 g-1), and antioxidant activity (38-46%) compared to the Romaine type ’Nebras’. Conversely, the Romaine type exhibited higher shoot and root biomass and larger leaf area. These findings highlight that T. harzianum inoculation, particularly at the seed stage, enhances heat stress tolerance and improves both yield and quality traits in hydroponically grown lettuce.